Incentive Effects of the U.S. Welfare System: A Review - Moffitt, Robert (Journal of Economic Literature, 1992)
The author would like to acknowledge support for prior work on this topic from the U.S. Department of Health and Human Services, and helpful comments from three anonymous referees, Rebecca Blank, Howard Chernick, John Fitzgerald, Irwin Garfinkel, Peter Gottschalk, Edward Gramlich, David Greenberg, Judith Gueron, James Heckman, V. Joseph Hotz, Robert Hutchens, Michael Keane, Frank Levy, Larry Mead, Michael Murray, Robert Plotnick, Anuradha Rangarajan, Philip Robins, Howard Rolston, Jeffrey Smith, and Daniel Weinberg. All opinions and errors are those of the author alone.